1984
DOI: 10.1093/jn/114.9.1609
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Rate and Thyroid Status in Rats Fed Diets of Different Protein-Energy Value: The Importance of Free T3

Abstract: Oxygen consumption and thyroid hormone status have been investigated in relation to dietary protein and energy intake in young growing rats fed a control diet of 18% protein as well as diets containing 9 and 4.5% protein fed ad libitum and an 18% protein diet fed at a restricted intake for up to 14 days. Measurements of growth rate, food intake and oxygen consumption indicated that the rats fed a 4.5% protein diet ad libitum and those fed restricted amounts of an 18% protein diet have behaved similarly with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In addition. as we have described [9]. concentrations of free T 3 in the protein-deficient rat change in the opposite direction to total T 3 due to increases in binding proteins.…”
Section: Peripheral Mechanismssupporting
confidence: 50%
“…In addition. as we have described [9]. concentrations of free T 3 in the protein-deficient rat change in the opposite direction to total T 3 due to increases in binding proteins.…”
Section: Peripheral Mechanismssupporting
confidence: 50%
“…Fasting-induced changes in FT4 levels were most significant in female rats, and the decrease in FT4 levels in male rats was only appar ent after prolonged fasting (table 1). Serum total T3, the free T3 fraction, and serum free T3 all decrease during fast ing [1,42], Also, in rats fed a low protein, high carbohy drate diet, the serum free T3 fraction decreases [43][44][45][46], These changes are due to an increased production o f a T3-binding globulin [41][42][43] and are most significant in young rats [45].…”
Section: Discussionmentioning
confidence: 97%
“…As shown in figure 1, total serum proteins of young malnourished preg nant rats were lower than in the virgin con trols; this might imply higher amounts of free circulating thyroid hormones (especially T3) in these animals. On the other hand, Cox et al [21] found low basal metabolic rates associated with high total (but low free) se rum T3 levels in young rats fed a low (4%)-protein diet during 14 days, suggesting that in young rats maintained on a low-protein intake there is an increase in the serum bind ing capacity of T> There are conflicting data in the literature with regard to the effects of malnutrition on the thyroid function of adult rats [22,23].…”
Section: Discussionmentioning
confidence: 99%